Developing ESP based-digital learning materials support students’ needs at Indonesian vocational schools: Perceived quality - Fadlia, Fadlia; Asra, Surya; Zulida, Evi; Santosa, Made Hery (Universitas Islam Negeri Banda Aceh, 2022)
The purpose of incorporating digital learning materials into vocational school English instruction is to assist students in acquiring specific competencies. Additionally, prepared digital learning materials are intended to assist teachers in developing instructional materials that follow the principles of English for Specific Purposes (ESP) in vocational high schools (SMK). The research used the qualitative research and development (R&D) method. The stages of developing this teaching material model are adapted from Thiagarajan, Semmel, and Semmel's 4Ds model (1974), which consists of four stages: define, design, develop, and disseminate. As data sources, the participants were two teachers from two different vocational schools with a combined enrolment of 115 students. This research's results are a model for developing digital-based teaching materials (prepared digital learning materials). Furthermore, it was discovered that using the prepared digital learning materials greatly aided teachers in teaching English to achieve specific competencies. From the students' perspective, they admitted that it was also exciting because they perceived learning as distinct from traditional learning materials due to digital materials usage.